Evaluation of three intravenous injectable anaesthesia protocols in healthy adult male alpacas. (21st September 2017) - Taylor, Sandra D; Baird, Aubrey N; Weil, Ann B; Ruple, Audrey
Abstract : Few studies have investigated the effects of intravenous injectable anaesthesia in alpacas. The objective of this study was to evaluate three intravenous injectable anaesthesia protocols in healthy adult alpacas exposed to noxious stimulation. A prospective randomised crossover study was done using six healthy adult male alpacas. Cardiopulmonary variables including heart rate, respiratory rate, mean arterial pressure, end‐tidal pCO2 and haemoglobin oxygen saturation were collected immediately after and every two minutes following induction of each of three anaesthesia protocols in six male castrated alpacas. A hoof tester was used to apply consistent pressure every two minutes after induction and the response was recorded. Time from induction to muscle contraction and leg withdrawal were recorded, as well as time from induction to extubation, sternal recumbency and standing. There was no significant difference in duration of anaesthesia or cardiopulmonary variables among the three anaesthesia protocols. Total duration of anaesthesia was approximately 20 minutes for each protocol. Hypoxaemia and mild hypercarbia were common among all protocols. Induction and recovery scores were excellent.